Sustainable strategy of green open space in reducing stress levels in urban areas - Nababan, Abdi Nusa Persada; Ambarini , Lina Anandari Dwi (Journal of Placemaking and Streetscape Design, 2025)
Background: Cities around the world are facing increasing challenges related to high levels of stress in urban areas. One strategy that has been proposed to overcome this problem is the development of Green Open Space with a sustainable approach. This study aims to evaluate the impact and effectiveness of sustainable strategies for developing green open spaces in reducing stress levels in urban areas, with the City of East Jakarta. Methods: The systematic literature review involves searching for previous research that focuses on the relationship between green open spaces and mental health. Findings: The research results show that developing green open spaces with a sustainable approach can significantly reduce stress levels in urban areas. The people of East Jakarta indicate that the existence of green open spaces provides an effective escape from the stresses of daily life, as well as improving their overall quality of life. Improving the quality of green open spaces and sustainable development can create an environment that supports the mental and physical health of urban communities. Conclusion: Collaborating with community participation in the planning process, as well as continuing to conduct research to understand more deeply the positive impact of green open space on the welfare of urban communities so that a sustainable strategy for developing green open space can become a strong foundation for creating a city that is healthier and friendlier to stress levels and hopefully can make an important contribution to sustainable urban development efforts in terms of psychological well-being. Novelty/Originality of this article: This study highlights the significant role of sustainable green open space development in reducing urban stress levels, emphasizing community involvement and continuous research as key factors for fostering a healthier and more livable city.